ALGORITHM OF OPERATIONAL RISK ASSESSMENT OF BULGARIAN POSTS PLC: ALGORITHM OF OPERATIONAL RISK ASSESSMENT OF BULGARIAN POSTS PLC - Stoyanov, Anatoli; Kazakov, Stefan; Kodzheykova, Veselina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report examines the main activities of the management technology of Bulgarian Posts and defines the organization and factors of management processes. The proposed algorithm aims to validate these interconnected relationships that make up a logistics system. An approach was adopted for mathematical modeling of operations and criteria for evaluating socio-economic indicators.